Chromaticity effects in microlensing by wormholes - Eiroa, Ernesto Fabian (2001)
We discuss the possibility that the stellar system Cyg OB2 No. 5 can be a gamma-ray source in the light of recent EGRET and radio data. This system is formed by an O7 Ia + Ofpe/WN9 contact binary. A third star, probably a B0 V star also associated with the system, is located at ∼1700 AU from the primary. We estimate the expected gamma-ray luminosity from the colliding winds region, the terminal shock of the wind, and the Chromaticity effects introduced by the finite source size in microlensing events by presumed natural wormholes are studied. It is shown that these effects provide a specific signature that allow to discriminate between ordinary and negative mass lenses through the spectral analysis of the microlensing events. Both galactic and extragalactic situations are discussed.